Artificial Gravity as a Countermeasure to the Cardiovascular Deconditioning of Spaceflight: Gender Perspectives - Evans, Joyce M.; Knapp, Charles F.; Goswami, Nandu (Frontiers in Physiology, 2018)
Space flight-induced physiological deconditioning resulting from decreased gravitational input, decreased plasma volume and disruption of regulatory mechanisms is a significant problem in returning astronauts as well as in normal aging. Here we review effects of a promising countermeasure on cardiovascular systems of healthy men and women undergoing Earth-based models of space-flight. This countermeasure is produced by a centrifuge and called artificial gravity (AG). Numerous studies have determined that AG improves orthostatic tolerance (as assessed by various protocols) of healthy ambulatory men, of men deconditioned by bed rest or by immersion (both wet and dry) and, in one case, following spaceflight. Although a few studies of healthy, ambulatory women and one study of women deconditioned by furosemide, have reported improvement of orthostatic tolerance following exposure to AG, studies of bed-rested women exposed to AG have not been conducted. However, in ambulatory, normovolemic subjects, AG training was more effective in men than women and more effective in subjects who exercised during AG than in those who passively rode the centrifuge. Acute exposure to an AG protocol, individualized to provide a common stimulus to each person, also improved orthostatic tolerance of normovolemic men and women and of furosemide-deconditioned men and women. Again, men’s tolerance was more improved than women’s. In both men and women, exposure to AG increased stroke volume, so greater improvement in men vs women was due in part to their different vascular responses to AG. Following AG exposure, resting blood pressure (via decreased vascular resistance) decreased in men but not women, indicating an increase in men’s vascular reserve. Finally, in addition to counteracting space flight deconditioning, improved orthostatic tolerance through AG-induced improvement of stroke volume could benefit aging men and women on Earth.